Water washing and acid washing of gasification fly ash from municipal solid waste: heavy metal behavior and characterization of residues - Qin, Junde (2023)
Gasification fly ash (GFA) is a hazardous solid residue generated in the slagging-gasification of municipal solid waste (MSW). GFA contains higher amounts of heavy metals such as Pb and Zn than incineration fly ash (IFA), which increases the difficulty of heavy metal immobilization but simultaneously makes it a potential feedstock for metal recovery. Water washing and acid washing are conventional and economic methods to treat wastes with high heavy metal and chloride contents. However, the research on the effects of such methods in treating GFA is still blank. Hence, in this study, water washing and acid washing of GFA were investigated in detail. Heavy metal behaviors at different time points during the washing processes were studied in a wide pH range and comprehensive characterizations of washed GFAs were also conducted. The results show that different re-precipitates could be identified in washed GFAs depending on different pH conditions. After water washing for 24 h, more than 60% of Zn in GFA would dissolve and re-precipitate into calcium zincate. It is also revealed that the precipitation effect could in turn influence the pH during the washing process. After acid washing with a low-concentration acid, heavy metal leachabilities were found reduced due to the pH and precipitation effect. High-concentration acid washing could effectively extract Zn and Cd with extraction ratios exceeding 90%. Applying 1.2 M-HCl washing, a short washing period of 15 min could realize a Pb extraction ratio of 81.2%, much higher than 53.2% when extending the washing period to 24 h.